Efficiency Enhancement through Optimization on Sequence Path Defining and Temporal Streamlining of Coupled Networks - Murugan, Chitra; Kittappa, Thiagarajan; Karthikeyan, M.; Anburaja, Anish (Migration Letters, 2023)
The optimization of coupled linear networks is a pervasive challenge with diverse applications across scientific and engineering disciplines. This study delves into recent research efforts aimed at enhancing the performance and efficiency of interconnected systems characterized by linear relationships. The pursuit of algorithmic advancements stands as a cornerstone in this domain, with researchers focusing on the development of existing algorithms capable of swiftly addressing extensive linear systems arising from network interactions. An emerging trend involves linear network optimization. The proposed approach seamlessly integrates insights from numerical linear algebra, optimization, and graph theory, leading to accelerated computations and heightened accuracy. This synergistic interplay paves the way for transformative applications in fields like telecommunications, signal processing, and control systems. The robust optimization of linear coupled networks addresses the inherent uncertainties and variations that affect network performance in real-world scenarios.